Experimental investigation of mechanical and durability performances of self-compacting concrete blended with bagasse ash, metakaolin, and glass fiber - Wagh, Monali; Waghe, Uday; Bahrami, Alireza; Ansari, Khalid; Özkılıç, Yasin Onuralp; Nikhade, Anshul (Frontiers in Materials, 2024)
This study examines the effects of using bagasse ash (BA) and metakaolin (MK) together as substitutes for cement in self-compacting concrete (SCC), together with the addition of glass fiber (GF), on the physical and mechanical characteristics of the concrete. Eighteen SCC mixes were created, each containing different proportions of BA (0, 10, 15, and 20%), MK (0, 10, 15, and 20%), and BA and MK collectively (10% + 5% and 10% + 10%) as cement replacement with and without 0.1% of GF. Utilizing the results of the slump flow, T-500 slump flow, V-funnel, and L-box tests, the performance of fresh self-compacting concrete (SCC) was determined. Furthermore, the research study examined the SCC samples' strengths, durability, and microstructural properties. The SCC mix blended with 10% of BA and 5% MK reveals better flowability as the slump flow increases from 692mm to 715mm. A strong linear correlation was discovered between the slump flow values (mm) and V-funnel duration (sec), with R2 = 0.8876, and the blocking ratio (H2/H1), with R2 = 0.8467. At all the testing ages, the SCC mix blended with 10% BA, 5% MK, and 0.1% GF (SCC1B10M5) demonstrated the highest degree of strength qualities. At 56 days, the 10% BA, 5% MK, and 0.1 GF mix had 12.8, 25.7, and 22.2% higher compressive, flexural, and splitting tensile strengths (STSs) than the control mix. SCC, combined with BA, MK, and GF, outperformed the control mix. After immersion in a 3% H2SO4 solution, the SCC mix containing 10% BA, 5% MK, and 0.1% GF experienced a minimum reduction in weight loss and UPV of 1.01% and 3.1%, respectively. Additionally, there was a decrease of 29.4% in the percentage of charges passed. The ideal composition was achieved by incorporating 10% BA, 5% MK, and 0.1% GF into the SCC mixture, resulting in a dense structure without any visible pores or cracks during microstructural analysis.